(untitled) (Fiep Bulletin - online, 2013)
The population of Sao Gabriel da Cachoeira is formed in 97% of Indians, from 22 ethnic groups in the region belonging to the families and linguistic Kwell, Cordell, Maku and Yanomami, approximately 10% of the Brazilian indigenous population. Identify and map the areas of recreation, the sights and the natural beauty of Sao Gabriel da Cachoeira oportunizarão register them and disseminate them to the national and international scene. Audiovisual tools, standardized interview were used in this research field-raised in the discipline curriculum Leisure and Recreation: Educational and Technical Aspects of the Course of Physical Education at the University of the State of Amazonas. The equipment in the city of Sao Gabriel da Cachoeira, identified and mapped are: Micro equipments specialist; Equipment average of versatility addressed: Leisure Spaces Public Schools (State School Indigenous Sister Agnes Penha; College St. Gabriel College and John D. Marchesi) ; Agrotécnica Federal School, University of the State of Amazonas; House Sister Agnes Penha - Rescue and Recovery Program of Cultural; Projects tucum; Kunhatai UKA Suri; Maniaki; Seed; Project Animation Parish); Site Don Bosco Youth; Macro equipaments multipurpose: the Spa the Tigre, Barroso - Site Putira, of Bromyard, Beaches: Great, Jaú Island of the Sun; From social tourism: 5 hotels, 2 of troops; 4 Lan Houses, the natural attractiveness of Sao Gabriel da Cachoeira (Sleeping Beauty; rapids – Isle of Adana; rock formations; Waterfall of Coraci; Sunset; Leisure Spaces of Indigenous Communities: Areal; Glastonbury Mirim; Good Hope; Waruá; Ceware; Camanaus, and the Religious Festivals, and The Festival of the High River Indian Tribes Black - Festribal; gathering Baré and Tukan. However, we lack of public regulate geared to the planned completion of the free time of the employee, resident or visitor, the public power should be denied.